Crystallization speed and solidification time of sodium acetate trihydrate–graphite composite phase change materials during solidification. (August 2021) - Huang, Haotian; Zhang, Yue; Wu, Honglin; Lin, Jianquan; Zhao, Qian; Zhou, Tiecheng; Xiao, Yimin
Highlights: Solidification and temperature change of SAT under supercooling are studied. Crystallization speeds and solidification times of shaped SAT are tested. Solidification time is used to control heat release in solidification model. Solidification rate is independent of EG ratio and nucleating agent. Abstract: Sodium acetate trihydrate (SAT) is an excellent phase change material (PCM) with a high heat storage capacity. However, its application is limited by supercooling. Existing solidification models with supercooling track the crystallization front and thus determine each grid's solidification degree and temperature. Therefore, crystallization speed directly determines the discharge characteristics of the solidification process under supercooling. However, this parameter has not yet been determined for the SAT compound, which is more commonly used than pure SAT. In addition, the heat release rate after crystallization is triggered cannot be determined via only the crystallization front as this would yield erroneous results. To address this problem, solidification time is incorporated into the solidification model in this study. First, the relationship between SAT solidification and temperature change is investigated via experiments. Then, different proportions of composited PCMs comprising SAT and expanded graphite (EG) are configured, and their crystallization speeds and solidification times under different states are tested. The results show that these two properties are only correlated with temperature, and exhibit no evident relationship with the EG ratio or addition of a nucleating agent. The data are incorporated into empirical formulas and used in a one-dimensional model. The simulation results are in good agreement with the experimental data from a previous study, thus indirectly proving the accuracy of the experimental results.